(untitled) (Patrimônio e Memória, 2025)
This article analyses the recognition of the former Maceió Public Prison as a state prison heritage site. The study examines the process of urban consolidation of the city centre in the 19th century, a period in which foundational structures such as the church, the pillory, the town hall and the jail were established. Inaugurated in 1817, the public jail functioned until the 20th century, when, due to overcrowding, the prisoners were transferred to the São Leonardo Prison. In the 1970s, the building was demolished because the jail represented a spurious element, standing out from the urban core of the centre, characterised by its collection of historic buildings, public institutions and intense commercial activity. In this context, urban growth and the demand for new roads prompted road interventions associated with the construction of the Rei Pelé Stadium, prioritising urban mobility and the expansion of the city’s automobile network. Although a listing request was filed with IPHAN in 1966, the building was not recognised as a heritage site worthy of safeguarding, being considered a monument of ‘sad memory’. Through documentary sources, iconographic records and oral accounts with people who frequent Independence Square, the research reveals that the space is still socially identified as ‘Jail Square’, demonstrating that, even after its destruction, the memory of the prison persists discreetly among the site’s users. The article discusses the limits of traditional heritage policies, emphasising that the preservation of buildings such as prisons is not a neutral action, but rather an instrument of symbolic power. Listing has the potential to legitimise certain memories while silencing others, becoming a political gesture to confront the past. The study proposes the revalorisation of this historical legacy, highlighting the importance of transmitting memory to new generations.